2016
DOI: 10.3109/02656736.2016.1147617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patchouli alcohol on the regulation of heat shock-induced oxidative stress in IEC-6 cells

Abstract: Purpose Patchouli alcohol (PA) is used to treat gastrointestinal dysfunction. The purpose of this study was to ascertain the function of PA in the regulated process of oxidative stress in rat intestinal epithelial cells (IEC-6). Materials and methods Oxidative stress was stimulated by exposing IEC-6 cells to heat shock (42 °C for 3 h). IEC-6 cells in treatment groups were pretreated with various concentrations of PA (10, 40, and 80 ng/mL) for 3 h before heat shock. Results Heat shock caused damage to the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In the present study, the mRNA expression of GSH-px and CAT was increased in TCM treatment groups, which indicated that TCM could regulate the activity of GSH-px and CAT to help resist heat stress by increasing the mRNA expression of antioxidants. Similar results were obtained in a previous study, which found that the mRNA expression of GSH-px and CAT was increased in suitable TCM treatment groups (Liu et al, 2016). The reasons for the increase of GSH-px and CAT expression caused by the addition of TCM may be that TCMs used in our experiment have anti-oxidant functions, such as Astragalus membranceus and hawthorn (Li et al, 2010;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the mRNA expression of GSH-px and CAT was increased in TCM treatment groups, which indicated that TCM could regulate the activity of GSH-px and CAT to help resist heat stress by increasing the mRNA expression of antioxidants. Similar results were obtained in a previous study, which found that the mRNA expression of GSH-px and CAT was increased in suitable TCM treatment groups (Liu et al, 2016). The reasons for the increase of GSH-px and CAT expression caused by the addition of TCM may be that TCMs used in our experiment have anti-oxidant functions, such as Astragalus membranceus and hawthorn (Li et al, 2010;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The production of oxygen free radicals and the accompanying damage to the organism are controlled by antioxidant defense systems (Aggarwal et al, 2013). Catalase (CAT) and glutathione peroxidase (GSH-px) are two important antioxidants in the body (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(II) As an in vitro study, Liu et al demonstrated that PA reversed heat stress-stimulated Keap 1 and HO-1 mRNA expressions promotion in cultured IEC-6 (rat intestinal epithelial cell), and the modulatory effects of PA on injured cell by oxidative stress were superior to that of glutamine [65]. (III) Considering that inflammation and oxidative injury interacted with each other, both anti-inflammatory and antioxidative activities of PA were investigated in UV radiation-induced cutaneous photoaging mice [66] and in ethanol, indomethacin, and stress-induced ulcer rats [67].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%